2020
DOI: 10.1158/1541-7786.mcr-19-0638
|View full text |Cite
|
Sign up to set email alerts
|

Growth-Inhibitory Activity of Bone Morphogenetic Protein 4 in Human Glioblastoma Cell Lines Is Heterogeneous and Dependent on Reduced SOX2 Expression

Abstract: Glioblastoma multiforme (GBM) continues to have a dismal prognosis. Even though detailed information on the genetic aberrations in cell signaling and cell cycle checkpoint control is available, no effective targeted treatment has been developed. Despite the advanced molecular defects, glioblastoma cells may have remnants of normal growth inhibitory pathways, such as the bone morphogenetic protein (BMP) signaling pathway. We have evaluated the growth inhibitory effect of BMP4 across a broad spectrum of patient … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…Our own observations align closely with the work of Dalmo et al, 2020. We observed that exposure of glioblastoma TPCs (5 primary lines) to BMP2/4 resulted in rapid downregulation of SOX2 followed by reduction in Ki67 and induction of GFAP (Fig.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our own observations align closely with the work of Dalmo et al, 2020. We observed that exposure of glioblastoma TPCs (5 primary lines) to BMP2/4 resulted in rapid downregulation of SOX2 followed by reduction in Ki67 and induction of GFAP (Fig.…”
Section: Introductionsupporting
confidence: 90%
“…In contrast, Dalmo et al, 2020 concluded that response is heterogenous among 40 primary human glioblastomas analyzed [5]. Invariably, such response in sensitive cells induced SMAD1/5/9 phosphorylation, SMAD4 expression, and consistent downregulation of SOX2 [5].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Temozolomide (TMZ) was chosen as the standard‐of‐care drug and added at a concentration found in the cerebrospinal fluid of GBM patients (1 µg/ml), to reflect a clinically relevant dose (Ostermann et al , 2004). The cytokine BMP4 was chosen for its inhibitory effect on GBM growth (Piccirillo et al , 2006; Dalmo et al , 2020) and was administered at a dosage (1 ng/ml) shown to elicit a receptor response (Heemskerk et al , 2019) and to have an effect on cell fate choice (Lim et al , 2000), while not causing a complete stop of cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…This was ascribed to reduction in self-renewal through the induction of asymmetric cell division, diminishing the CSC pool, and pushing cells into mature post-mitotic states. 55 However, extensive heterogeneity has been observed in BMP4 responsiveness in other studies, 56,57 highlighting the importance of assessing therapeutic responses across multiple CSC populations.…”
Section: Csc Signaling Networkmentioning
confidence: 99%